POSISI PASAR BANK PEMBANGUNAN DAERAH SULAWESI - Dedy Takdir Syaifuddin (JEP (Jurnal Ekonomi Pembangunan), 2017)
This study aims to determine the competitive market position between the Sulawesi Regional Development Bank which consists of South Sulawesi BPD, Central Sulawesi BPD, North Sulawesi BPD and Southeast Sulawesi BPD. The results showed that the construct of the latent variable market share with indicators; Current account share, market share savings, market share deposits and market share credit, generally occupied by the South Sulawesi BPD as the market leader, then followed by North Sulawesi BPD which occupies the position of the challenger market, and Southeast Sulawesi BPD which occupies the position follower market, as well as BPD Central Sulawesi which occupies the position as the market nicher. While in terms of performance latent variables with indicators; return on assets (ROA), return on equity (ROE), net interest margin (NIM), and operating costs on operating income (BOPO) generally place North Sulawesi BPD as the leader market, followed by Southeast Sulawesi BPD which occupies the position the challenger market, then followed by the South Sulawesi BPD which occupied the position as the follower market and Central Sulawesi BPD which occupied the position as the market nicher.